Attitude of Basic Science Medical Students towards Post Graduation in Medicine and Surgery: A Questionnaire based Cross-sectional Study from Western Region of Nepal (Nepal Journal of Epidemiology, 2011)
Background Career choice of medical students plays a vital role for health care system of a country. It also plays a crucial role to bring medical specialties into mainstream focus. Materials and Method A cross-sectional, questionnaire-based study has been performed at Manipal College of Medical Sciences, during the period of 1st May to 31st August–2011. A self reported questionnaire was given to the undergraduate medical students of Basic sciences. Questionnaire included career choices, nature of career, reason for choice, and education level and occupation in their parents. Results Data was collected from 269 medical students, among them 145 males and 124 female students participated in the study. The mean age of Indian (85, 31.6%), Nepalese (110, 40.9%) and Sri Lankan (74, 27.5%) students were 18.3 ± SD 0.7, 18.6 ± SD 0.8 and 18.0 ± SD 1.5 years respectively. Education and Occupation of parents seems to influence the determination of career choice in case of Medical students (p